Three‐dimensional helical computed tomography in prenatal diagnosis of fetal skeletal dysplasia. (14th July 2013) - Macé, G.; Sonigo, P.; Cormier‐Daire, V.; Aubry, M.‐C.; Martinovic, J.; Elie, C.; Gonzales, M.; Carbonne, B.; Dumez, Y.; Le Merrer, M.; Brunelle, F.; Benachi, A.
ABSTRACT Objectives (1) To study the use and diagnostic value, as a complement to ultrasound, of helical computed tomography (helical CT) to differentiate normal fetuses from cases of skeletal dysplasia; (2) to define the most relevant indications for helical CT; and (3) to evaluate its diagnostic performance with respect to radiological criteria considered discriminatory. Methods This was a retrospective study from 2005 to 2008 in 67 pregnant women who underwent helical CT after 26 weeks of gestation for suspected fetal skeletal dysplasia due to fetal shortened long bones on ultrasound (≤ 10thpercentile), either alone or associated with other bone abnormalities. The results were compared with pediatric examinations in 41 cases and with fetal autopsy findings after elective termination of pregnancy in the others. Results Helical CT had a sensitivity of 82%, specificity of 91% and positive and negative predictive values of 90% and 83%, respectively, for diagnosis of fetal skeletal dysplasia. An etiological diagnosis that had not been suspected at ultrasound was specified in 15% of cases and diagnoses suspected at ultrasound were confirmed in 24% and discounted in 43% of cases. The prevalence of skeletal dysplasia was increased in cases of micromelia < 3rd percentile or if there was a combination of bone signs. Helical CT showed 69% sensitivity in identifying individual predefined pathological bone signs which were confirmed on fetal autopsy findings. Conclusion Helical CT is a key examination, in combination with ultrasound, in the diagnosis of fetal skeletal dysplasia from 26 weeks of gestation. It should be reserved for cases with severe micromelia below the 3rd percentile and for those with micromelia ≤ 10th percentile associated with another bone sign. A checklist of discriminatory signs is proposed. Copyright © 2012 ISUOG. Published by John Wiley & Sons Ltd.